MODERNITAS DALAM PERSPEKTIF SEYYED HOSSEIN NASR - Tri Astutik Haryati (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2011)
This study examined the thought of Seyyed Hossein Nasr on modernity. Nasr confronted Western Metaphysicsí view on one side and Islamic Metaphysicsí view on the other. Nasr took more emphasis on Sufism, though Nasr himself seemed not yet to the level of a mystic Sufi figures as known in the Islamic world. However, Nasr indeed had his own originality-in certain limits-that he concocted Sufism he mastered with his experience and his study results in the West to find alternative answers to the problems of modern man.